The impact of magnesium content on lithium-magnesium alloy electrode performance with argyrodite solid electrolyte - Aspinall, J; Sada, K; Guo, H; Kotakadi, S; Narayanan, S; Chart, Y; Jagger, B; Milan, E; Brassart, L; Armstrong, D; Pasta, M (Springer Nature, 2024)
Solid-state lithium-based batteries offer higher energy density than their Li-ion counterparts. Yet they are limited in terms of negative electrode discharge performance and require high stack pressure during operation. To circumvent these issues, we propose the use of lithium-rich magnesium alloys as suitable negative electrodes in combination with Li6PS5Cl solid-state electrolyte. We synthesise and characterise lithium-rich magnesium alloys, quantifying the changes in mechanical properties, transport, and surface chemistry that impact electrochemical performance. Increases in hardness, stiffness, adhesion, and resistance to creep are quantified by nanoindentation as a function of magnesium content. A decrease in diffusivity is quantified with 6Li pulsed field gradient nuclear magnetic resonance, and only a small increase in interfacial impedance due to the presence of magnesium is identified by electrochemical impedance spectroscopy which is correlated with x-ray photoelectron spectroscopy. The addition of magnesium aids contact retention on discharge, but this must be balanced against a decrease in lithium diffusivity. We demonstrate via electrochemical testing of symmetric cells at 2.5 MPa and 30∘C that 1% magnesium content in the alloy increases the stripping capacity compared to both pure lithium and higher magnesium content alloys by balancing these effects.